2017
DOI: 10.1186/s12957-017-1271-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of enhanced recovery after surgery programs on laparoscopy-assisted gastrectomy for gastric cancer: a systematic review and meta-analysis of randomized control trials

Abstract: BackgroundThis meta-analysis is aimed to evaluate the feasibility and safety of enhanced recovery after surgery (ERAS) programs in gastric cancer patients undergoing laparoscopy-assisted gastrectomy (LAG).MethodsWe performed a meta-analysis of randomized control trials involving either enhanced recovery after surgery (ERAS)/fast track surgery (FTS) for patients underwent LAG. EMBASE, Pubmed, Web of science, and Cochrane Library were searched. Primary outcomes included the length of postoperative hospital stay,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 45 publications
(37 reference statements)
3
31
0
1
Order By: Relevance
“…Our analysis demonstrated an increased rate of readmission in the ERAS arm, a contentious finding that was also shown by Ding et al [36]. This trend, albeit non-significant, was also seen in other meta-analyses [37,38,41]. As this is contrariwise to the goals of ERAS to attenuate surgical stress and promote recovery, further research is warranted to investigate this antithetical phenomenon.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our analysis demonstrated an increased rate of readmission in the ERAS arm, a contentious finding that was also shown by Ding et al [36]. This trend, albeit non-significant, was also seen in other meta-analyses [37,38,41]. As this is contrariwise to the goals of ERAS to attenuate surgical stress and promote recovery, further research is warranted to investigate this antithetical phenomenon.…”
Section: Discussionsupporting
confidence: 84%
“…Our findings demonstrate that the ERAS program resulted in shorter length of hospital stay (LOS), reduced hospital costs, reduced time to return of gut function, without compromising on risks of morbidity and mortality; however, an increased rate of readmission was observed in the ERAS arm, a finding not demonstrated in previous meta-analyses. Furthermore, there were weaknesses in these studies [35][36][37][38][39][40][41][42][43]. All except one meta-analysis [38] included only randomized controlled trials (RCTs); Li et al [37] only examined laparoscopic gastrectomy; Ding et al [36] limited their analysis to English language articles.…”
Section: Discussionmentioning
confidence: 99%
“…To date, gastric cancer (GC) is still one of the most lethal and common cancers worldwide, which is often associated with a high mortality and morbidity (17)(18)(19). The majority of GC patients are diagnosed at an advanced stage and receive a poor prognosis (20).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the current state of the ERAS protocol in the field of gastric cancer surgery, four meta‐analyses have been published in or since 2017 (Table ) . Li et al and Li et al focused on the outcomes of ERAS in patients undergoing laparoscopic gastrectomy.…”
Section: Current Status and Future Prospects Of Eras For Gastric Cancmentioning
confidence: 99%
“…Li et al and Li et al focused on the outcomes of ERAS in patients undergoing laparoscopic gastrectomy. They also showed that ERAS contributed to shorter postoperative hospital stay, rapid postoperative recovery, and decreased cost without increasing complications or readmission rate among patients undergoing laparoscopic gastrectomy . Ding et al and Wang et al focused on the outcomes of ERAS in patients undergoing gastrectomy .…”
Section: Current Status and Future Prospects Of Eras For Gastric Cancmentioning
confidence: 99%